FOREIGN EXPERIENCE IN SCIENTIFIC RESEARCH («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article examines the foreign experience of conducting scientific research, drawing upon a literature review and interviews with 15 researchers who have worked internationally. The foreign research experience, while challenging, offers valuable opportunities for advancing scientific knowledge and fostering global cooperation. Future research should explore discipline-specific factors and the long-term impacts of international experience on researchers' careers.
Keywords: international research, scientific collaboration, research challenges, cultural differences, research funding